Banking Corporation Dividend Policy – Evidence from ASEAN-6 Countries - Ruth Samantha Hamzah; Efva Octavina Donata Gozali; Putiriva Reihani Yurdi (Accounting Analysis Journal, 2022)
Purpose : The study aims to investigate the effect of Return on Assets (ROA), Asset Turnover (Ast-Tvr), Leverage, Change in Earnings (ChE), and Size on dividend policy as measured by Dividend Increase (DIC) on banking companies in Asean-6 Countries. Method : We employed eight-year observation period from 2012 to 2019, thus the purposive method obtained 134 companies as samples. This study used regression analysis by Logistic Regression as the method and collected the secondary data from the annual financial statements of banking companies of ASEAN-6 countries which comprises of Indonesia, the Philippines, Singapore, Malaysia, Thailand, and Vietnam. Findings : The results show that ROA, Ast-Tvr, Leverage, ChE, and Size have no significant effect on dividend policy. Novelty : To the best of our knowledge, there is no literature examining dividend policy in ASEAN-6 countries. Hence, we tried to fill the gap in terms of dividend policies in ASEAN-6 Countries. Further, this study contributes further research to provide evidence of what policies are set by banking corporations in ASEAN countries. This research also displays a better understanding for stakeholders and investors in interpreting the dividend related information prior taking the investment decision. Keywords : Dividend Policy; ROA; Asset Turnover; Leverage; Change in Earnings; ASEAN-6 Countries